Evaluations of Inflammatory Status in Chronic Renal Failure Patients Undergoing Hemodialysis and Conservative Treatment - Fatimah Kadhim Ibrahim AL- Mahdawi1 , Ali Shalash Sultan2 , Nabeel Khalid Mohamed Ali AL-Wandi3 , Ma (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: - Chronic inflammation is a basic feature of end stage kidney disease and is associated withincreasing risk of mortality and morbidity in patients undergoing dialysis.The aim: - the study amid toevaluate white blood cells and IL-6 in patients undergoing hemodialysis and without hemodialysis. Methodsand Subjects:- The study was designed on 106 patients with chronic renal failure age range (20-69years).The patients divided in two groups according to treatment, 40 patients with conservative treatment and66 patients with hemodialysis treatment. IL-6 were determined by using a commercially available ELISAMicro wells kit. Total white blood cells count and differential count were determined by using an automatedhematology autoanlyzer XT2000i. Results:- showed a significant (p<0.05) decrease of total white bloodcells count, neutrophils, lymphocytes, monocytes, eosinophils and basophils in hemodialytic group whencompared with conservative group. But IL-6 levels was higher significantly (p<0.01) in hemodialytic groupwhen compared with conservative group. Conclusion: - hemodialysis session impaired immune system andactivated anti-inflammatory factors.